1994
DOI: 10.1111/j.1439-0388.1994.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into traditionally managed Djallonké‐sheep production in the humid and subhumid zones of Asante, Ghana

Abstract: This studies presented in this paper were undertaken on 42 households units in two ecological zones of four farming villages located in the heart of the Kumawu Traditional Area (KTA) in Asante. The traditional area is the largest (9256 km(2) ) of the 21 traditional areas or paramouncies comprising the Asante Region (24 390 km(2) ), one of the ten regions of Ghana. The headquarters are in the township of Kumawu, which is located 56 km north-east of Kumase, the capital of the Asante Region. A brief discription o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…In the current study, the animals born from the second, third and fourth parturition showed the best growth performance than animals born from the first and the fifth lambing rank. Our findings are in accordance with the reports of several authors (Fall et al, 1982;Poivey et al, 1982;Filius et al, 1986;Abaffa et al, 1992;London et al, 1994;Yapi-Gnaoré et al, 1997).This remark can be due to the age and the live weight of primiparous ewes because the females do not usually reach their physiological maturity at the first lambing and their own growth competes with that of their product (Poivey et al, 1982;and Yapi-Gnaoré al., 1997).…”
Section: Effect Of Lambing Rank:-supporting
confidence: 94%
“…In the current study, the animals born from the second, third and fourth parturition showed the best growth performance than animals born from the first and the fifth lambing rank. Our findings are in accordance with the reports of several authors (Fall et al, 1982;Poivey et al, 1982;Filius et al, 1986;Abaffa et al, 1992;London et al, 1994;Yapi-Gnaoré et al, 1997).This remark can be due to the age and the live weight of primiparous ewes because the females do not usually reach their physiological maturity at the first lambing and their own growth competes with that of their product (Poivey et al, 1982;and Yapi-Gnaoré al., 1997).…”
Section: Effect Of Lambing Rank:-supporting
confidence: 94%
“…In order to reduce the gap between the demand and meat production, increased efforts have been put into livestock development in West Africa over the last decade, with emphasis on Djallonke sheep (Bonfoh et al, 1996;London et al, 1994;Yapi-Gnaoré et al, 1997). In the Republic of Benin, attempts have been made to improve meat production of Djallonke sheep through genetic manipulation and improved management.…”
Section: Introductionmentioning
confidence: 98%
“…There is, however, a dearth of documented information regarding what farmers themselves collectively perceive as "feed for small ruminants" in the transitional zone. Moreover, there is no documentation regarding the relative importance of these feeds to farmers in the zone, although some researchers reported on feeds eaten by small ruminants in parts of the zone [ 17 , 18 ]. There is also a dearth of information on the modalities of feed usage by farmers in the zone, with respect to who uses which feed, feed sources, how different feeds are used and the seasonality of usage.…”
Section: Introductionmentioning
confidence: 99%